Evasão escolar nos cursos técnicos do PROEJA na rede federal de educação profissional e tecnológica de Minas Gerais - Priscila Rezende Moreira (2012)
This study was developed under the Masters program of the Post-Graduation Program in Education of the Federal University of Minas Gerais College of Education. Its goal was to identify factors that influence school dropout in technical courses of the National Program for the Integration of Professional Education and Basic Education within Youth and Adult Education (PROEJA) in the Federal Network of Professional and Technological Education of Minas Gerais (RFEPT-MG). This program, launched in the country in 2005, represented a significant growth on the supply of professional education in the federal school network for youths and adults. However, the PROEJA faces a high dropout rate: in 2010, the technical courses dropout rate, in the RFEPT of Minas Gerais, reached 30.9% of the number of students enrolled in those courses. In order to achieve the proposed goal of this project, a research was performed, having it been divided into four stages. The first of them consisted of a bibliographic review on school dropout, Youth and AdultEducation, and PROEJA. The second involved an analysis of information regarding PROEJA's enrollment/dropout rates in Minas Gerais, which was obtained from the National System of Information on Professional and Technological Education (SISTEC-SETEC/MEC). The third stage was comprised of a self-administered questionnaire for dropout students of RFEPT-MG's PROEJA/Technical Education, and the fourth and last stage was the analysis of those questionnaires' answers. The results of the research show that most of the answerers, PROEJA's technical courses dropouts, are aged between 18 and 35 (74.8%), are male (55.7%), black(52.8%), single (50.4%), and have children (58%). Most of the dropouts did not return to their studies after deciding to leave the course, even though they wish to complete the technical training offered by PROEJA. The answerers have quit school due to personal reasons, such as the difficulty of managing study and work schedules (66%), the need to work (64.4%), the fact that the school is far from home and/or workplace (63.6%), because they had financial difficulties to undertake the course(54.7%), and also because they lacked motivation to keep studying (50.8%). In regards to the factors linked to the school context, a percentage above 30% has abandoned because of the lack of financial aid (47.6%) and of schedule flexibility to study the subjects (45.9%), also because of the excess of subjects within the course (32.3%) and overly demanding teachers (30.9%). The set of factors that has contributed to the decision of dropping out of PROEJA is very diverse; it relates to specifical issues of each individual's situation, but also to the courses' structure for complying with the peculiarities of the subjects placed within the universe called youth and adult education.